2022
DOI: 10.1101/2022.07.21.500964
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex differences in default mode network connectivity in healthy aging adults

Abstract: Women show an increased lifetime risk of Alzheimer's disease (AD) compared to men. Characteristic brain connectivity changes, particularly within the default mode network (DMN), have been associated with both symptomatic and preclinical AD, but the impact of sex on DMN function throughout aging is poorly understood. We investigated sex differences in DMN connectivity over the lifespan in 595 cognitively healthy participants from the Human Connectome Project - Aging cohort. We used the intrinsic connectivity di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Women rely upon specific DMN edges for memory performance; connections between the bilateral pIPL and the two greatest hubs of the DMN, the mPFC and the PCC/precuneus are the strongest predictors. Our prior work suggests that women have relatively increased within-DMN connectivity compared with men, particularly in posterior nodes and particularly during perimenopausal decades (Ficek-Tani et al ., In press). Reliance upon intra-DMN edges for memory performance likely has its advantages: we and others have shown that DMN connectivity, particularly between posterior nodes, correlates with memory task performance (Fredericks et al ., 2019; Natu et al ., 2019; Kang et al ., 2021; Vanneste et al ., 2021; Ficek-Tani et al ., In press), and the literature consistently demonstrates that women outperform men across the lifespan in tests of verbal episodic memory (Bleecker et al ., 1988; Herlitz, Nilsson and Bäckman, 1997; Golchert et al ., 2019).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Women rely upon specific DMN edges for memory performance; connections between the bilateral pIPL and the two greatest hubs of the DMN, the mPFC and the PCC/precuneus are the strongest predictors. Our prior work suggests that women have relatively increased within-DMN connectivity compared with men, particularly in posterior nodes and particularly during perimenopausal decades (Ficek-Tani et al ., In press). Reliance upon intra-DMN edges for memory performance likely has its advantages: we and others have shown that DMN connectivity, particularly between posterior nodes, correlates with memory task performance (Fredericks et al ., 2019; Natu et al ., 2019; Kang et al ., 2021; Vanneste et al ., 2021; Ficek-Tani et al ., In press), and the literature consistently demonstrates that women outperform men across the lifespan in tests of verbal episodic memory (Bleecker et al ., 1988; Herlitz, Nilsson and Bäckman, 1997; Golchert et al ., 2019).…”
Section: Discussionmentioning
confidence: 98%
“…This work adds to the growing literature suggesting that women rely more on the DMN than do men both at rest and during memory task performance. At rest, women have relatively higher DMN connectivity (Biswal et al ., 2010; Scheinost et al ., 2015; Cavedo et al ., 2018; Ritchie et al ., 2018; Ficek-Tani et al ., In press), with higher posterior DMN connectivity particularly during the menopausal decades (Ficek-Tani et al ., In press); this increased connectivity correlates with better performance on tests of short-term memory (Fredericks et al ., 2019; Natu et al ., 2019; Kang et al ., 2021; Vanneste et al ., 2021; Ficek-Tani et al ., In press). This profile is similar to individuals with preclinical (amyloid-β +) or elevated genetic risk (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations